Codebook: Social Networking over Code - Begel, Andrew; DeLIne, Robert (Proceedings of ICSE 09 (New Ideas and Emerging Results), 2009)
Social networking systems help people maintain connections to their friends, enabling awareness, communication, and collaboration, especially at a distance. In many studies of coordination in software engineering, the work artifacts, e.g. code, bugs, specifications, are themselves the objects that link engineers together. In this paper, we introduce Codebook, a social networking web service in which people can be “friends” not only with other people but with the work artifacts they share with them. Providing a web interface to the graph of these connections will enable software engineers to keep track of task dependencies, discover and maintain connections to other teams, and understand the history and rationale behind the code that they work on and use.